Primary school teachers’ beliefs about teaching mathematics - Palu, Anu; Kikas, Eve (NOMAD Nordic Studies in Mathematics Education, 2007)
The main aim of the study was to investigate the beliefs about the purposes and methods of teaching mathematics in primary school teachers with different teaching experience. The sample consisted of 103 practicing teachers and 26 pre-service teachers. It was shown that teachers with different teaching experience were concordant in their evaluations of the purposes of teaching mathematics – they evaluated the purpose of acquiring knowledge higher than the purpose of the development of personality. Also, all groups of teachers valued formalist teaching methods the least. However, teachers with different teaching experience held different beliefs about using traditional, formalist and social teaching methods.